The green impact of livestock-based nutrient management - Ehui, Simeon K. (Food and Agriculture Organization of the United Nations, 1999)
Concerns about the generation of greenhouse gases, biodiversity loss, overgrazing and desertification of dry lands and the maintainance of soil and water quality are increasing as human populations grow. This paper discusses what the role livestock can contribute to these problems. Studies showed that livestock production contributed only about one percent of carbon dioxide emissions in Africa in 1993. Livestock and manure management contribute about 16 percent of the total annual production of methane worldwide. Emissions are highest where both animal production and feed quality are low, indicating that research to increase productivity through use of improved feeding strategies would reduce methane emissions from ruminants. The paper also discusses environmental concerns and outlines factors that can contribute to protecting the environment including research in ruminant genetics and health; and policy. Research at ILRI shows that livestock can play a vital role in meeting both productivity and sustainability objectives. This paper also highlights some of the contributions.